The use of gene-based technologies for talent identification in high-performance sport - McGregor, B.
The use of gene-based technologies as a talent identification method is beginning to receive greater attention as knowledge about the human gene map becomes more apparent. This introduces an ethical dilemma and has re-ignited the age-old debate of nature versus nurture.